Հայերէն անծանօթ հրատարակութիւններ - Մինասեան, Միհրան Ա․ (տպ. Atlas)
The author describes 50 books and booklets which were published between 1861 and 1920, and are not listed in any Armenian book bibliographies. The books belong to the rich collection of Dr. Haig Demoyan (Yerevan). These books were published in different cities both in and outside historic al Armenia, like Tbilisi, Constantinople, St. Petersburgh, Tehran, Moscow, Kantsag, Alexandropole and , particularly , in different cities of the USA, like New York, Boston, Rox bury, Providence and Philadelphia. The books have diverse contents. Some are by -laws of Armenian political parties, compatriotic unions, and other organizations. Others are historic al, musical, medical, literary -poetic, or song books textbooks, calendars , etc. Many of the authors are unknown , and the existence of any other publications by them are unknown too. Others, however, are known names , and these books add to their literary legacy. These new ly found books help the comprehensive study of the history of Armenian printing as some of the printing houses mentioned in this article are not mentioned in any Armenian bibliographies.
Keywords: Մատենագիտութիւն; Հայ տպագիր գիրք